The effect of using aids in learning some badminton skills for female students - mondil, mohamed; Shukr, Louay (Journal of Physical Education, 2023)
The importance of the research is the use of auxiliary tools in addition to preparing special exercises and knowing their impact on learning some badminton skills, as well as the use of auxiliary tools reduces the teaching time and reduces the effort exerted by the teacher and the learner in the education process. And the inability to perform the basic skills correctly, so it was necessary to use auxiliary tools and exercises designed to help students in learning some badminton skills, as the study aimed to design exercises using auxiliary tools in learning some badminton skills. Statistical significance between the pre and post tests for the control and experimental groups in learning some skills in badminton, in addition to that there are statistically significant differences between the control and experimental groups in the post tests in learning some skills in badminton for female students, and the research community represents first-stage female students in the College of Physical Education and Science The pre-tests and the exploratory experiment were conducted on the students of the first stage, after which s The researcher applied the educational curriculum, then conducted the post-tests, collected the results and processed them statistically, and the researcher came out with several conclusions, the most important of which are the exercises designed using the auxiliary tools that had a major role in controlling the performance of some badminton skills of the experimental group